2022
DOI: 10.3390/pr10061050
|View full text |Cite
|
Sign up to set email alerts
|

Production, Optimization, and Partial Purification of Alkali-Thermotolerant Proteases from Newly Isolated Bacillus subtilis S1 and Bacillus amyloliquefaciens KSM12

Abstract: Proteases that can remain active under extreme conditions such as high temperature, pH, and salt concentration are widely applicable in the commercial sector. The majority of the proteases are rendered useless under harsh conditions in industries. Therefore, there is a need to search for new proteases that can tolerate and function in harsh conditions, thus improving their commercial value. In this study, 142 bacterial isolates were isolated from diverse alkaline soil habitats. The two highest protease-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Among these strains, B. amyloliquefaciens TSA-2 showed maximum protease activity at pH 9, which indicated that it could be producing alkaline proteases. Similar observations were made in previous studies on Bacillus species, which also showed peak protease production at pH 8 and 9 [14]. Furthermore, B. amyloliquefaciens TSA-2 produced the most protease at a temperature of 40-45°C, suggesting that these bacteria were mesophilic.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Among these strains, B. amyloliquefaciens TSA-2 showed maximum protease activity at pH 9, which indicated that it could be producing alkaline proteases. Similar observations were made in previous studies on Bacillus species, which also showed peak protease production at pH 8 and 9 [14]. Furthermore, B. amyloliquefaciens TSA-2 produced the most protease at a temperature of 40-45°C, suggesting that these bacteria were mesophilic.…”
Section: Discussionsupporting
confidence: 89%
“…However, an increase in temperature beyond this range resulted in a reduction in protease synthesis, indicating that high temperatures disrupted the molecular structure of the bacteria, causing them to stop producing proteases. Other studies have suggested that the ideal temperature for protease generation in Bacillus subtilis is 37°C [14]. In the case of B. amyloliquefaciens TSA-2, a 24-hour incubation period was found to be ideal for maximum protease synthesis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The most important group of enzymes so far used are the alkaline serine proteases [6]. Alkaline proteases as additives are *Corresponding Author Institutional Email: Najafpour@nit.ac.ir (G. Najafpour Darzi) extensively used in pharmaceuticals, dehairing of leather, textile, food and detergent industries [7,8]. The major sources of alkaline proteases consist of plants, animal organs and microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial proteases represent two-thirds of commercial proteases worldwide [ 5 ]. Microorganisms are preferred over the others for the large-scale production of many enzymes for the following reasons: they are present everywhere in nature; they can be produced in relatively higher quantities than in plants and in animals; they grow quickly and simply; they have unique physiological and biochemical properties, as well as simple culture conditions; they are produced by cells of easy manipulation [ 6 , 7 ]; and they are secreted from microorganisms, facilitating the down streaming stages. Moreover, the proteolytic enzymes found in microbes are small, dense, and structurally spherical and have many applications in various industrial sectors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%